An Image Sharing Technique Using QR Code Through Cloud for Mobile Devices - Aysha Farina, N; P George, Jossy; Varghese Kureethara, Joseph (International Journal of Engineering and Technology, 2018)
Image sharing is a very important task in the digital communication. Images of various resolutions are transferred every moment electronically. Cloud computing and associated security concerns motivate every increasing research in this field. This paper is about an image sharing technique using the famous Quick Response (QR) Code which is very popular now. We have a web application also associated with this.